Preface to the Special Issue “Ecologically sustainable fishing”: Project KESKALA background, objectives and conclusions - Lehtonen, H.; Estlander, S.; Horppila, J.; Nurminen, L.; Olin, M.; Rask, M.; Ruuhijärvi, J.; Tiainen, J. (Boreal Environment Research Publishing Board, 2024)
(No abstract)